(3GdJagje dChGFd UfGYI GdJfLjes - (3eMeO Hf CMeO, CHh GdQjMGf GdHjQhfj GdNhGQRej,J (B440 (3g` s
(3ChdgG (B:s
(3HYO GdYfhGf(B: (3Ef GdEMGWg HgPg GdYGde hcjajI Tcd GdSeGA hGdCQV heG HjfgeG Ydi hLgg GdCNHGQ GdeCNhPI HGdJbdjO fGaYg LOkG ai UfGYI GdJfLje dCf HgG s
(3BNQgG (B:s
(3abO LgdgG GdefJSHhf EdjgG aVdkG Yf GdefJajf YfgG s
(3ajgG cKjQ ef GdLOGhd ef GdQShes
(3bhHdJ Ydi fSNI UMjMI SfI (B871s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B205s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B22 s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdadcs